Kat and Meg conquer the world - Priemaza, Anna (HarperTeen, an imprint of HarperCollins Publishers, 2017)
When they are thrown together for a year-long science project, Kat, who has a social anxiety disorder, and Meg, who has ADHD, bond over their common obsession with a swoon-worthy online gaming star.